Synthesis of some new triazene and diazene derivatives and in vitro evaluation of preliminary antitumor activities - (:unkn) unknown (My University, 2007)
In this study, a number of novel triazene and diazene derivatives (1a-g) were designed and synthesized by utilizing the coupling of diazonium salts of 5-(4-aminophenyl)-2,4-dihydro-4-allyl-3H-1,2,4-triazole-3-thione, 4-aminobenzoic acid, sulfanilamide, sulfathiazole, benzocaine, sulfaguanidine and sulfadiazine containing an aromatic primary amine group with N-methylaniline. The structures of the synthesized compounds were confirmed by the spectral data (UV, IR, 1H-NMR) and elemental analysis. Testing of preliminary antitumor activity of these compounds in vitro against Huh-7 liver cancer cell demonstrated 4-allyl-5-[4-(3-methyl-3-phenyltriaz-1-enyl)phenyl]-2,4-dihydro-3H- 1,2,4-triazole-3-thione compound 1a and 4-(3-methyl-3-phenyltriaz-1-enyl) benzenesulfonamide compound 1c to have inhibitory activity.
Keywords: Diazene; Synthesis; Triazene